Analisis Debit Banjir Rancangan Sub DAS Air Bengkulu Menggunakan Analisis Frekuensi dan Metode Distribusi - Gusta Gunawan Gunawan; Besperi Besperi; Liza Purnama (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2020)
Abstract The Design discharge is the important data needed for design of the water infrastructure. The purpose of this study is to estimate the design discharge with a variety of times using a frequency analysis in the Air Bengkulu Sub-watershed. Rain fall data were obtained from the BMKG of Bengkulu province, its starting from 2009 to 2018 years. The design flood estimation method used a statistical method. It is using the distribution method. The initial stage of the research is to process rain data and then conduct frequency analysis. The mathematical equation for frequency analysis includes statistical equations to determine the average value, standard deviation, coefficient of variation, skewness coefficient and kurtosis coefficient. The method used in determining the type of distribution for frequency analysis in this study uses the Gumbel Type I distribution method, Pearson Log Type III, Normal, and Normal Log. Distribution fit test was performed with chi square test and Kalmogorof Smirnov test. The results of estimated design discharges for the 2 years return period, 5 years return period, 10 years return period, 25 years return period, 50 years return period and 100 years returns period in the Air Bengkulu down stream Sub-watershed are respectively 125.16 m3 / sec (2 years return period), 145.24 m3 / sec (5 years return period), 157.59 m3 / sec (10 years return period), 172.43 m3 / sec (25 years return period), 183.03 m3 / sec (50 years return period) and 193.34 m3 / sec (100 years return period). Keywords: watershed, Air Bengkulu, Design Discharge, Frequency Analysis, Distribution Analysis